2019
DOI: 10.3390/cells8121585
|View full text |Cite
|
Sign up to set email alerts
|

H2O2 as a Feedback Signal on Dual-Located WHIRLY1 Associates with Leaf Senescence in Arabidopsis

Abstract: Leaf senescence, either as a natural stage of development or as an induced process under stress conditions, incorporates multiple intricate signaling pathways. At the cellular level, retrograde signals have been considered as important players during the initiation and progression of senescence in both animals and plants. The plant-specific single-strand DNA-binding protein WHIRLY1 (WHY1), a repressor of leaf natural senescence, is dually located in both nucleus and plastids. Despite many years of studies, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 65 publications
(105 reference statements)
2
29
0
Order By: Relevance
“…For example, WHIRLY1, which belongs to a small plant-specific family of DNA/RNA binding proteins, has been proposed to move from the chloroplast to the nucleus in response to environmental cues, such as high light intensity (Foyer et al, 2014; Świda-Barteczka et al, 2018). However, it did not seem to be translocated from chloroplasts to the nucleus, but rather it was more likely that the WHIRLY1 protein comprised two isoforms localized in the chloroplasts and the nucleus, respectively (Lin et al, 2019). The dual functions of WHIRLY1 may be associated with its dual localization for coordination of the retrograde signaling from plastids to the nucleus (Ren et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For example, WHIRLY1, which belongs to a small plant-specific family of DNA/RNA binding proteins, has been proposed to move from the chloroplast to the nucleus in response to environmental cues, such as high light intensity (Foyer et al, 2014; Świda-Barteczka et al, 2018). However, it did not seem to be translocated from chloroplasts to the nucleus, but rather it was more likely that the WHIRLY1 protein comprised two isoforms localized in the chloroplasts and the nucleus, respectively (Lin et al, 2019). The dual functions of WHIRLY1 may be associated with its dual localization for coordination of the retrograde signaling from plastids to the nucleus (Ren et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It also has chaperone functions in RNA processing in chloroplasts (Pfalz et al, 2006;Prikryl et al, 2008;Meloneck et al, 2010;Świda-Barteczka et al, 2018). WHY1 is also associated with the thylakoid membrane and has putative functions in photosynthesis (Isemer et al, 2012;Foyer et al, 2014;Comadira et al, 2015;Huang et al, 2017;Guan et al, 2018;Lin et al, 2019). An earlier study on knockdown maize ZmWhy1 mutants, which have a pale green phenotype (Prikryl et al, 2008) suggested that WHY1 is involved in chloroplast biogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…All three WHY proteins bind single-stranded DNA, and perhaps RNA, in a sequence-nonspecific manner (Desveaux et al, 2002;Bach-Pages et al, 2020). WHY1 is partitioned between the nucleus and chloroplast (Krause et al, 2005;Grabowski et al, 2008); however, the mechanisms that might determine its distribution in the cell are only starting to emerge (Ren et al, 2017;Lin et al, 2019). In the nucleus, WHY1 controls the expression of transcription factors, defense genes, and senescence genes by binding their promoters (Krupinska et al, 2013;Ren et al, 2017).…”
mentioning
confidence: 99%
“…To establish which of the two WHY1 isoforms affects SA metabolism, the authors complemented why1 with plastid, nuclear, or the full-length WHY1 isoforms (Lin et al, 2019). Full-length WHY1 has both a plastid-target peptide for plastid import and a nuclear localization signal.…”
mentioning
confidence: 99%
See 1 more Smart Citation